An Experimental Analysis of Kenikir for Optimal Lactation : The Effectiveness of Cosmos Caudatus Extract on Postpartum Maternal Prolactin Hormone Levels - Sulistiyah Sulistiyah; Retno Dewi Prisusanti (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Insufficient milk supply is one of the primary reasons for the discontinuation of exclusive breastfeeding, which poses a significant challenge to maternal and infant health. While kenikir (Cosmos caudatus) has long been used as a traditional remedy believed to help increase breast milk production, its direct effect on lactation has not been thoroughly studied. This research aimed to evaluate the impact of kenikir extract on prolactin hormone levels in postpartum mothers, which plays a key role in milk production. This was a true experimental study utilizing a pretest-posttest control group design. Kenikir extract served as the independent variable, and prolactin hormone levels were the dependent variable. A total of 40 postpartum mothers were included in the study, randomly divided into two groups: an intervention group that received 300 mg of kenikir extract daily for 14 days, and a control group with no treatment. The study analyzed within-group changes using the Paired T-Test and Wilcoxon test, and between-group differences were compared using the Mann-Whitney test. The results indicated that the intervention group experienced a significant increase in prolactin hormone levels, with an average of 44.70 ng/ml and a p-value of 0.0001. This shows that kenikir extract significantly enhances prolactin hormone secretion in postpartum mothers. These findings suggest that kenikir extract could be a promising natural remedy for increasing milk supply, offering an alternative or complementary approach to supporting lactating mothers. Further studies should be conducted to explore the long-term effects of kenikir extract on breastfeeding success and its potential role in promoting maternal and infant health.